Factores de riesgo y transmisión vertical en niños de madres seropositivas años 2017-2018 Hospital Regional de Loreto Punchana 2021 - Cespedes Isla, Carmen Rossmery (2023)
The objective of this research was to determine the relationship between risk factors and vertical transmission of HIV in children born to seropositive mothers between the years 2017-2018. The study was non-experimental, quantitative, descriptive, correlating, cross-sectional and retrospective, the information collected corresponds to the years 2017 and 2018. The sample consisted of 60 children exposed to HIV born to seropositive mothers. The following techniques were used: the documentary review of the medical records, the record book and follow-up of the mother and the exposed child, the notification and follow-up sheet of the mother and the exposed child, used by the epidemiology office of MINSA-Peru. The instrument used was a verification form of risk factors and vertical transmission, it had a validity of 90%. The results indicate that 6.7% of children infected with HIV presented a positive PCR from mothers with high viral load and 55.0% of children with negative PCR were from mothers with a low viral load. It is concluded that the risk factors related to the vertical transmission of HIV in the present study were the viral load of the mothers and breastfeeding and mixed breastfeeding, with p= 0.022 and p=0.000, respectively.